Molecular mechanisms underlying the evolution of a color polyphenism by genetic accommodation in the tobacco hornworm, Manduca sexta - Yuichiro Suzuki; Stephanie Amaya; Paula Gonzalez; Daniela Becerril; Surisadai Aquit; Maya Davis; Madeline Hoesel; Elizabeth Chou; Hesper Khong; Kathryn Zaia; Heidi S. Park; H. Frederik Nijhout; et al. (Proceedings of the National Academy of Sciences, 2025)
How organisms evolve under extreme environmental changes is a critical question in the face of global climate change. Genetic accommodation is an evolutionary process by which natural selection acts on novel phenotypes generated through repeated encounters with extreme environments. In this study, polyphenic and monophenic strains of the black mutant tobacco hornworm, Manduca sexta , were evolved via genetic accommodation of heat stress-induced phenotypes, and the molecular differences between the two strains were explored. Transcriptomic analyses showed that epigenetic and hormonal differences underlie the differences between the two strains and their distinct responses to temperature. DNA methylation had diverged between the two strains potentially mediating genetic assimilation. Juvenile hormone (JH) signaling in the polyphenic strain was temperature sensitive, whereas in the monophenic strain, JH signaling remained low at all temperatures. Although 20-hydroxyecdysone titers were elevated under heat shock conditions in both strains, the strains did not differ in the titers. Tyrosine hydroxylase was also found to differ between the two strains at different temperatures, and its expression could be modulated by topical application of a JH analog. Finally, heat shock of unselected black mutants demonstrated that the expression of the JH-response gene, Krüppel-homolog 1 ( Kr-h1 ), increased within the first 30 min of heat shock, suggesting that JH levels respond readily to thermal stress. Our study highlights the critical role that hormones and epigenetics play during genetic accommodation and potentially in the evolution of populations in the face of climate change.